RETRACTED: Sustainable Human Resource Management: A Transformation Perspective of HRM Functions Through Optimized Artificial Intelligence - Arif Furqon Nugraha Adz Zikri; Sunu Widianto; Rita Komaladewi (School of Business, Bogor Agricultural University (SB-IPB), 2024)
We hereby announce the retraction of the article titled “Sustainable Human Resource Management: A Transformation Perspective of HRM Functions Through Optimized Artificial Intelligence”, Vol. 10 No. 2, Mei 2024. This retraction is due to the discovery that the article had been previously published in BISMA (Bisnis dan Manajemen, which constitutes a violation of our policy on duplicate publication. The document pertaining to the article, including its content and any supplementary materials, has been retracted from the Jurnal Aplikasi Bisnis Dan Manajemen (JABM). Consequently, it is imperative to undertake reasonable measures to expunge all references to this article.